PENGEMBANGAN KEMASAN BAKSO TAKEAWAY - Daulay, Nurul Hidayah; Fajrah, Nofriani (LPPM Universitas Putera Batam, 2023)
The packaging is also easily damaged, making it difficult for consumers to bring meatballs when they are going. The plastic packaging used less able to protect the product, and packaging in the form of a bowl that uses a heat sealer also makes the product easy to spill because the lid on the packaging is not tightly locked. The purpose this research is to develop meatball packaging according to the packaging design criteria desired and needed by consumers. The method used the Quality Function Deployment. The results obtained the packaging design criteria that have the highest priority are the shape of the packaging and the basic materials of the packaging with an importance value of 5, while the packaging design criteria that have the lowest priority are the spacing label area with an importance value 3. The technical response with the highest priority is the availability of a seal on the packaging cover with technical importance rating 216, the absolute importance 72, relative importance 10.23%. The technical response with the lowest priority is the appropriate label layout so that the product label is easy to see the technical importance rating 72, absolute importance 24 and relative importance 3.41%